2020
DOI: 10.1186/s13063-020-04814-0
|View full text |Cite
|
Sign up to set email alerts
|

Cov-hep study: heparin in standard anticoagulation based on citrate for continuous veno-venous hemodialysis in patients with COVID-19: a structured summary of a study protocol for a randomized controlled trial

Abstract: Objectives The primary objective is to test if heparin added to a standard regional anticoagulation protocol based on citrate is able to reduce dialysis circuit losses by clotting without increasing the risk of thrombocytopenia or bleeding, in patients with COVID-19 with acute kidney injury requiring dialysis. Trial design Randomized, parallel-group, open-label trial, with two arms (ratio 1:1) comparing different continuous renal replacement therapy anticoagulation strategies. Participants Eligibility cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…COVID-19 can cause damage to organs such as the liver, kidneys, and myocardium, and then develop into multifunction organ failure [ 20 ]. Our study also showed that the levels of total bilirubin, urea nitrogen, and creatinine were significantly different among the 3 groups, and gradually increased with progression of the disease, which is consistent with previous research results [ 21 ]. However, there was no significant difference in the results of alanine aminotransferase (ALT) and glutamic oxaloacetic transaminase (AST) among the 3 groups.…”
Section: Discussionsupporting
confidence: 92%
“…COVID-19 can cause damage to organs such as the liver, kidneys, and myocardium, and then develop into multifunction organ failure [ 20 ]. Our study also showed that the levels of total bilirubin, urea nitrogen, and creatinine were significantly different among the 3 groups, and gradually increased with progression of the disease, which is consistent with previous research results [ 21 ]. However, there was no significant difference in the results of alanine aminotransferase (ALT) and glutamic oxaloacetic transaminase (AST) among the 3 groups.…”
Section: Discussionsupporting
confidence: 92%
“…In line with our results, Shankaranarayanan et al showed that most superior filter life was reached during combined regional citrate and systemic heparin anticoagulation. A prospective trial comparing regional citrate anticoagulation with systemic heparin anticoagulation during CRRT in patients with COVID-19 is ongoing and should provide results at the end of 2021 [ 21 ]. Limited evidence shows a higher anticoagulation efficacy of direct thrombin inhibitor, argatroban in patients with COVID-19 treated with CRRT [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, a multicentre study of consecutive patients with COVID-19 receiving CRRT showed that 83% of the patients lost at least one filter during CRRT [ 102 ]. Reinforcement of the anticoagulation strategy by adding heparin to a standard regional anticoagulation with citrate has been proposed [ 103 ].…”
Section: Venous Thrombosis During Covid-19 In the Ckd Populationmentioning
confidence: 99%